Evaluating effectiveness and cost-effectiveness of a group psychological intervention using cognitive behavioural strategies for women with common mental disorders in conflict-affected rural Pakistan: study protocol for a randomised controlled trial - Anna Chiumento; Syed Usman Hamdani; Muhammad Naseem Khan; Katie Dawson; Richard A. Bryant; Marit Sijbrandij; Huma Nazir; Parveen Akhtar; Aqsa Masood; Duolao Wang; Mark van Ommeren; Atif Rahman (Trials, 2017)
Abstract Background The impact of humanitarian disasters upon mental health is well recognised. The evidence for psychological interventions for mental health is mounting, but few interventions have been rigorously tested in humanitarian settings. To be sustainable in humanitarian settings interventions need to be short, simple, deliverable by nonspecialists under supervision, and adopt a transdiagnostic approach where an array of mental health outcomes are addressed simultaneously. These elements have been incorporated into the newly developed WHO Problem Management Plus (PM+) Group intervention. The aim of this trial is to evaluate the locally adapted PM+ Group intervention for women in Swat, Pakistan. Methods This PM+ Group trial is a two-arm, single-blind, cluster randomised controlled trial conducted in a community-based setting with women in rural Pakistan. PM+ is delivered in partnership with the Lady Health Worker (LHW) Programme which provides community-based health care to women in Pakistan. Thirty-four LHW clusters will be randomised in a 1:1 allocation ratio using a permuted-block randomisation method. Participants screened and found to meet the inclusion criteria will be allocated to either the PM+ intervention group (n = 306), or the control arm (n = 306). The manualised PM+ intervention involves five sessions, each lasting 3 h, and introduces four strategies applied by participants to problems that they are facing. It is delivered by local female facilitators with a minimum of 16 years of education who are provided with targeted training and supervision. The primary outcome is individual psychological distress, measured by levels of anxiety and depression on the Hospital Anxiety and Depression Scale at 20 weeks after baseline. Secondary outcomes include major depression, post-traumatic stress disorder, levels of social support, levels of functioning, and economic effectiveness. Intervention acceptability will be explored through an embedded qualitative study. Discussion The PM+ Group trial will provide important evidence on the effectiveness of an empirically supported psychological treatment delivered by nonspecialists in a humanitarian setting. If proven effective, the qualitative component will inform strategies for PM+ Group scale-up in health systems in other humanitarian settings. Trial registration Australian New Zealand Clinical Trials Registry, identifier: ACTRN12616000037404. Registered on 19 January 2016; WHO Protocol ID RPC705, v.4, 2 November 2015.